USING LEAST SIGNIFICANT BIT TECHNIQUE IN STEGANOGRAPHY TO HIDE INFORMATION - haikal, Fikri; Badria, Lailatul; Hendrawan, Aurellia Aknesia; Muharram, Muhammad Raihan; Gibran, M Khalil (JURNAL TEKNISI, 2025)
Abstract: In the digital information era, Steganography is a technique and art of hiding digital information and data behind other digital information, so that the real digital information is not visible. This study discusses the application of the Least Significant Bit (LSB) technique in steganography to hide information in image media. The LSB technique allows the insertion of secret messages into images by utilizing the least significant bits of the image pixels, so that the changes that occur are invisible to the human eye and do not arouse suspicion. This study explores the effectiveness of the LSB technique in maintaining data confidentiality, as well as analyzing image quality after information insertion. The results of the study indicate that the LSB technique can be used effectively to hide information without sacrificing the visual quality of the image, making it an attractive solution in the field of data communication security. In addition, this study also discusses the advantages and disadvantages of the LSB technique, as well as the possibility of developing this technique to improve data security in various applications.Keywords: data security; least significant bit (LSB) technique; steganography.Abstrak: Di era informasi digital, Steganografi merupakan teknik dan seni menyembunyikan informasi dan data digital di balik informasi digital lainnya, sehingga informasi digital yang sebenarnya tidak terlihat. Penelitian ini membahas penerapan teknik Least Significant Bit (LSB) dalam steganografi untuk menyembunyikan informasi di dalam media gambar. Teknik LSB memungkinkan penyisipan pesan rahasia ke dalam gambar dengan memanfaatkan bit paling signifikan dari piksel gambar, sehingga perubahan yang terjadi tidak terlihat oleh mata manusia dan tidak menimbulkan kecurigaan. Penelitian ini mengeksplorasi efektivitas teknik LSB dalam menjaga kerahasiaan data, serta menganalisis kualitas gambar setelah penyisipan informasi. Hasil penelitian menunjukkan bahwa teknik LSB dapat digunakan secara efektif untuk menyembunyikan informasi tanpa mengorbankan kualitas visual gambar, menjadikannya solusi yang menarik di bidang keamanan komunikasi data. Selain itu, penelitian ini juga membahas kelebihan dan kekurangan teknik LSB, serta kemungkinan pengembangan teknik ini untuk meningkatkan keamanan data di berbagai aplikasi.Kata Kunci: keamanan data; teknik least significant bit (LSB); steganografi.